(untitled) - Caplan, Priscilla (Chicago, 2003)
Metadata, or "data about data, " is used to organize and access information in an effective way. From cataloging to organizing archives, metadata helps frontline librarians provide customers with a direct path to information.
Keywords: Metadata,Information organization